2018
DOI: 10.1002/tsm2.38
|View full text |Cite
|
Sign up to set email alerts
|

Single-joint eccentric knee extension training preferentially trains the rectus femoris within the quadriceps muscles

Abstract: Eccentric contraction‐induced quadriceps strains, particularly in the rectus femoris (RF), frequently occur in sports. By using MRI‐based transverse relaxation time (T2) as an index of exercise‐induced muscle edema, previous studies found pronounced damage in RF after an acute single‐joint eccentric knee extension exercise. This study examined whether single‐joint eccentric knee extension training would preferentially train RF, resulting in greater hypertrophy of RF than the other quadriceps muscles. Twelve ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…only the overhead condition is fine). On the other hand, there is some evidence that single‐joint (Maeo, Shan, Otsuka, Kanehisa, & Kawakami, 2018) and multi‐joint (Kubo, Ikebukuro, & Yata, 2019) exercises preferentially train biarticular and monoarticular muscles, respectively, the former of which is supported by this study. Thus, a combination of overhead elbow extension (single‐joint exercise) and lying dumbbell press (multi‐joint exercise) may further promote hypertrophy of the Whole‐TB.…”
Section: Discussionsupporting
confidence: 80%
“…only the overhead condition is fine). On the other hand, there is some evidence that single‐joint (Maeo, Shan, Otsuka, Kanehisa, & Kawakami, 2018) and multi‐joint (Kubo, Ikebukuro, & Yata, 2019) exercises preferentially train biarticular and monoarticular muscles, respectively, the former of which is supported by this study. Thus, a combination of overhead elbow extension (single‐joint exercise) and lying dumbbell press (multi‐joint exercise) may further promote hypertrophy of the Whole‐TB.…”
Section: Discussionsupporting
confidence: 80%
“…They observed an increase in the volume of the gluteal and three vasti muscles; however, the hypertrophy of RF was not significant for either squat regimen. Similar findings were noted by Earp et al [ 12 ] and Zabaleta-Korta et al [ 13 ], where parallel squat RT resulted only in an increase in CSA of the vasti muscles, suggesting that for targeting the RF muscle, single-joint exercises may be a better option [ 14 ]. However, some of the recent studies have reported opposite results [ 15 , 16 , 17 ].…”
Section: Introductionsupporting
confidence: 82%
“…Throughout reconditioning (4-9.5 months; figure 2), we progressively integrated dynamic strength training (figure 9; online supplemental video 1) using predominately closed kinetic chain exercises except for the leg extensionspecifically to isolate eccentric knee extension. 38 Strength training biased the involved limb, progressively using a higher volume in unilateral strength exercises (ie, 5:2 sets ratio). 15 As neuromuscular performance deficits at joints other than the knee are associated with ACL injury risk, 39 40 we programmed accessory strength exercises (figure 9), and monitored isometric hip strength ( figure 7A).…”
Section: Strength Trainingmentioning
confidence: 99%
“…Throughout reconditioning (4–9.5 months; figure 2 ), we progressively integrated dynamic strength training ( figure 9 ; online supplemental video 1 ) using predominately closed kinetic chain exercises except for the leg extension — specifically to isolate eccentric knee extension. 38 Strength training biased the involved limb, progressively using a higher volume in unilateral strength exercises (ie, 5:2 sets ratio). 15 …”
Section: Gym-based Physical Preparationmentioning
confidence: 99%